Children's kinematic false memories - Ianì, Francesco; Limata, Teresa; Bucciarelli, Monica; Mazzoni, Giuliana (Journal of cognitive psychology (Hove, England), 2020)
Individuals misrecognise as seen the never-presented natural continuation of an action. These false memories derive from the running of kinematic mental models of the actions seen, which rest on motor inferences from implicit knowledge. We verified an implied prediction: kinematic false memories should be detectable even in children. The participants in our experiments first observed photos in which actors were about to perform actions on objects. At recognition they were presented with the original photos, plus (a) distractors representing the unseen natural continuation of the original actions, (b) distractors representing the beginning of other actions on the same objects and (c) distractors representing completed different actions on the same objects. In contrast to the original studies in which participants expressed their confidence in recognition, in our experiments the participants catgorirzed the action as seen or not seen. After replicating the original results with the dichotomous recognition task (Experiment 1), we detected spontaneous false memories also in children (Experiment 2).